Retours sur les manifestations juridiques du capital naturel - Alexandra Langlais (VertigO, 2018)
Over the last few years the concept of naturel capital has emerged as a key concept for influencing environmental decision-making choices. Intended to raise awareness of the limited state of our resources, it’s now also synonymous with the economic valuation of nature. This conception of nature is nevertheless considered to be simplistic insofar as it merely highlights the benefits provided to human society. Without mentioning this concept at the heart of the legal text, law nevertheless contributes to the development of tools to address these two complementary facets of natural capital.